MODVOLC: NEAR-REAL-TIME THERMAL MONITORING OF GLOBAL VOLCANISM - Wright R.; Flynn L.P.; Garbeil H.; Harris A.J.L.; Pilger E. (My University, 2004)
MODVOLC is a non-interactive algorithm developed at the Hawaii Institute of Geophysics and Planetology (HIGP) that uses low spatial resolution (1-km pixel-size) infrared satellite data acquired by the Moderate Resolution Imaging Spectroradiometer (MODIS) to map the global distribution of volcanic thermal anomalies in near-real-time. MODVOLC scans the Level-1B MODIS data stream, on a pixel-by-pixel basis, for evidence of pixel and sub-pixel-sized high-temperature radiators. Once a hot spot has been identified its details (location, emitted spectral radiance, time, satellite observation geometry) are written to ASCII text files and transferred via FTP to HIGP, from where the results are disseminated via the internet http://modis.higp.hawaii.edu). In this paper, we review the underlying principles upon which the algorithm is based before presenting some of the results and data that have been obtained since its inception. We show how MODVOLC reliably detects thermal anomalies at a large number of persistently and sporadically active volcanoes that encompass the full range of common eruptive styles including Erebus (Antarctica), Colima (México), Karymsky (Kamchatka), Popocatépetl (México), Etna (Italy), and Nyiragongo (Democratic Republic of Congo), amongst others. We also present a few cautionary notes regarding the limitations of the algorithm and interpretation of the data it provides.
Keywords: MODIS; MODVOLC; remote sensing; thermal monitoring